Physical Activity-Related Policy and Environmental Strategies to Prevent Obesity in Rural Communities: A Systematic Review of the Literature, 2002-2013 - Meyer, M. R. U.; Perry, C. K.; Sumrall, J. C.; Patterson, M. S.; Walsh, S. M.; Clendennen, S. C.; Hooker, S. P.; Evenson, K. R.; Goins, K. V.; Heinrich, Katie M.; Tompkins, N. O.; Eyler, A. A.; et al. (My University, 2016)
Introduction Health disparities exist between rural and urban residents; in particular, rural residents have higher rates of chronic diseases and obesity. Evidence supports the effectiveness of policy and environmental strategies to prevent obesity and promote health equity. In 2009, the Centers for Disease Control and Prevention recommended 24 policy and environmental strategies for use by local communities: the Common Community Measures for Obesity Prevention (COCOMO); 12 strategies focus on physical activity. This review was conducted to synthesize evidence on the implementation, relevance, and effectiveness of physical activity-related policy and environmental strategies for obesity prevention in rural communities. Methods A literature search was conducted in PubMed, PsycINFO, Web of Science, CINHAL, and PAIS databases for articles published from 2002 through May 2013 that reported findings from physical activity-related policy or environmental interventions conducted in the United States or Canada. Each article was extracted independently by 2 researchers. Results Of 2,002 articles, 30 articles representing 26 distinct studies met inclusion criteria. Schools were the most common setting (n = 18 studies). COCOMO strategies were applied in rural communities in 22 studies; the 2 most common COCOMO strategies were "enhance infrastructure supporting walking" (n = 11) and " increase opportunities for extracurricular physical activity" (n = 9). Most studies (n = 21) applied at least one of 8 non-COCOMO strategies; the most common was increasing physical activity opportunities at school outside of physical education (n = 8). Only 14 studies measured or reported physical activity outcomes (10 studies solely used self-report); 10 reported positive changes. Conclusion Seven of the 12 COCOMO physical activity-related strategies were successfully implemented in 2 or more studies, suggesting that these 7 strategies are relevant in rural communities and the other 5 might be less applicable in rural communities. Further research using robust study designs and measurement is needed to better ascertain implementation success and effectiveness of COCOMO and non-COCOMO strategies in rural communities.
Citation: Meyer, M. R. U., Perry, C. K., Sumrall, J. C., Patterson, M. S., Walsh, S. M., Clendennen, S. C., . . . Valko, C. (2016). Physical Activity-Related Policy and Environmental Strategies to Prevent Obesity in Rural Communities: A Systematic Review of the Literature, 2002-2013. Preventing Chronic Disease, 13, 24. doi:10.5888/pcd13.150406
Additional Authors: Valko, C.
Keywords: American-Indian Schoolchildren; Wellness Pilot Project; Action Schools; Bc; United-States; Elementary-Schools